2003
DOI: 10.1177/0011128702251043
|View full text |Cite
|
Sign up to set email alerts
|

Serious and Violent Young Offenders’ Decisions to Recidivate: An Assessment of Five Sentencing Models

Abstract: Five models of sentencing were assessed with respect to their impact on the decisions of young offenders to recidivate. The five sentencing models tested were fairness, deterrence, chronic offender lifestyle, special needs, and procedural rights. A sample of 400 incarcerated young offenders from the Vancouver, British Columbia, metropolitan area were asked questions regarding their attitudes toward these sentencing models and their intentions to recidivate after serving a period of incarceration. Principal com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 20 publications
1
18
0
1
Order By: Relevance
“…We cannot know whether the juveniles' introspections are accurate. However, a recent study with serious juvenile offenders found a correlation between their self-reported likelihood of committing a future offense and the number of offenses they committed after their release (Corrado et al, 2003), as did a recent study with adult offenders (Burnett, 2000). Some evidence indicates that the certainty of apprehension and punishment is important in deterring adult offenders (McCord, 1999), and the current study adds to the limited evidence that juvenile offenders may calibrate their behavior as a function of the perceived certainty of punishment (see Redding, 2003).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We cannot know whether the juveniles' introspections are accurate. However, a recent study with serious juvenile offenders found a correlation between their self-reported likelihood of committing a future offense and the number of offenses they committed after their release (Corrado et al, 2003), as did a recent study with adult offenders (Burnett, 2000). Some evidence indicates that the certainty of apprehension and punishment is important in deterring adult offenders (McCord, 1999), and the current study adds to the limited evidence that juvenile offenders may calibrate their behavior as a function of the perceived certainty of punishment (see Redding, 2003).…”
Section: Discussionmentioning
confidence: 74%
“…In a groundbreaking study, Bishop and Frazier (2000) conducted detailed interviews with 95 juvenile offenders in Florida about their comparative experiences in the juvenile and criminal justice systems, but did not specifically ask about their knowledge of transfer laws. Similarly, Corrado, Cohen, Glackman, and Odgers (2003) interviewed 400 serious and violent juvenile offenders about their perceptions of the fairness of their sentences and intent to recidivate, but the study was conducted in Canada with youths in the juvenile justice system who had not been tried as adults.…”
Section: Introductionmentioning
confidence: 99%
“…Further, in the Cambridge Study in Delinquent Development, Farrington et al [22] showed that while first convictions have a deviance amplifying effect consistent with a labeling effect, this effect wears off over time whether or not the individual is reconvicted. In fact, research suggests that contact with the criminal justice system may actually lower offenders' perceptions of being caught and convicted for their crime in the future (e.g., [13,69]). …”
Section: Desistance During the Adolescence-adulthood Transitionmentioning
confidence: 99%
“…Worthington, in particular, argues that the smaller the ÔÔinjustice gapÕÕ (i.e., the size of the difference between the magnitude of the original offense and the magnitude of the justice served) the easier it should be to forgive. The restorative justice literature makes a similar argument--that once justice is restored post-offense, mainly then can victims get over the offense (Corrado et al, 2003;Galaway and Judson, 1996).…”
Section: Choosing Alternatives To Revenge: the Importance Of The Sequmentioning
confidence: 99%